2004
DOI: 10.1207/s15327558ijbm1101_4
|View full text |Cite
|
Sign up to set email alerts
|

Depression, perceived control, and life satisfaction in university students from Central-Eastern and Western Europe

Abstract: The poor health and psychological well-being of people in the former socialist states of Centeral-Eastern Europe are of serious concern and may be related to low perceived control. We compared depressive symptoms, life satisfaction, and self-rated health in 3,571 male and female university students from 5 Western European countries and 4,793 students from 5 Central-Eastern European countries. Depression scores (short Beck Depression Inventory; Beck & Beck, 1972) were higher in Central-Eastern than Western Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 36 publications
8
61
2
Order By: Relevance
“…2 Low self-efficacy is seen in both depression and limited literacy. Individuals who suffer from depression report poor self-efficacy, plus low selfesteem, feelings of worthlessness, an external locus of control, and experience guilt or shame over their limitations [3][4][5][6][7] -some of the very same characteristics reported by individuals with limited literacy. 8 -10 Indeed, depression and limited literacy often coexist.…”
mentioning
confidence: 99%
“…2 Low self-efficacy is seen in both depression and limited literacy. Individuals who suffer from depression report poor self-efficacy, plus low selfesteem, feelings of worthlessness, an external locus of control, and experience guilt or shame over their limitations [3][4][5][6][7] -some of the very same characteristics reported by individuals with limited literacy. 8 -10 Indeed, depression and limited literacy often coexist.…”
mentioning
confidence: 99%
“…This suggests that cognitive distortion in depression is associated with greater social phobia and more negative expectations of social interactions. Depression may cause low self-efficacy, low self-esteem, feelings of worthlessness, an external locus of control, and experience guilt or shame over their limitations (Wardle et al, 2004;Beck, 2003). Hence, counselling should also focus on dealing with problems and issues related to distorted, negative and irrational thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of researches have proven that individuals who suffer from depression reported poor self-efficacy, low self-esteem, feelings of worthlessness, an external locus of control, and experience of guilt or shame over their limitations (Wardle et al, 2004;Beck, 2003). Elek and Grossman (2000) on the other hand pointed out that loneliness is related to depression.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies postulated that women in general are more prone to over report medical symptoms than men, [64,65]. Although, certain factors have been reported to increase stress and depression among university students, such as financial problemsand chronic ill health, [27,5], Consequently, there is a need for more research on students' depression, especially in a multi-ethnic nation like Nigeria.…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…However, there is a sharp contrast between income status among students in developing countries like Nigeria and those of developed countries. For instance, a study conducted among students from Spain and Germany, [65] found (72%) and (64%) of students respectively, reported their income to be always sufficient. In developed countries and in most western European countries, students especially university students receive financial aids, through government funding and bank loans which are not available for Nigerian students.…”
Section: Socio-economic Status and Social Supportmentioning
confidence: 99%